(untitled) (Indian Journal of Animal Production and Management, 2014)
A trial was conducted on 160 quails to evaluate the level of inclusion of Sheanut cake in the diets using four dietary treatments at (0%) T1, (3%) T2, (6%) T3 and (9%) T4 level of Sheanut cake at Poultry Experimentation Station, College of Veterinary Science Rajendranagar Hyderabad. Significantly (P<0.05) highest body weight gain was observed for T2 compared to other test diets. Feed consumption was significantly (P<0.05) highest in T2 compared to other test diets. Feed conversion efficiency was reduced with increased levels of Sheanut cake and the T2 diet was comparable to control diet. The performance of birds was comparable with control diet at 3% level of inclusion, although their performance was significantly reduced by inclusion of Sheanut cake at 6% and 9%.